(untitled) (Journal of Atomic and Molecular Sciences, 2018)
DFT and ab initio methods are used to investigate why the reaction, C(1)F3S(2)O2O(3)C(4)F2C(5)F3 + F−, results in the S-O cleavage chemospecifically. Three SN2 channels, i.e. S-O cleavage and back- and frontside of C-O scission are predicted to occur. The F(11) and F(12) atoms of the C(4)F2 group play the multiple roles in three paths. Multi-membered rings are formed in C-O rupture mechanisms due to the neighboring effect. The rate of S-O scission reaction is 1031 time as large as the rates of C-O rupture reactions. It is the combination of the irreversibility and the huge rate ratios to determine that S-O cleavage is chemospecific. This conclusion agrees well with the experimental results.